Design of small antennas for 400 MHz applications - Abdul Malek, Norun; Muhamad Mokhtar, Nur Hamizah; Ali, Khamis; Mohd. Isa, Farah Nadia; Abdul Rahman, Farah Diyana (IEEE, 2018)
In many wireless applications, antennas came with the majority of variable sizes. The interest for compact antennas in the industry have become high. Thus, the demand for small antenna is huge especially due to the booming industry of mobile communication. Generally, an antenna at low frequency exhibits in large physical size. This project investigates the design of an antenna at 400 MHz. The simulation of the antenna has been performed using CST MWS. Since medical applications are dealing with low frequency, it will lead to large size of antenna which brings a challenge for wireless personal area network (WPAN). Therefore, antenna miniaturization using Meander Line (ML) will be taking place to overcome the challenges. Thus, this paper presents a comparison between i) printed dipole antenna without meander line technique, ii) printed dipole with meander line technique and iii) printed monopole antenna with meander line technique. The results show that an estimation of reduction size by 50% can be achieved using Meander Line technique.